A short responsive interaction scale: construction and preliminary reliability and validity - Bhamani, Shelina; Merchant, Aliya; Nadeem, Sanober; Imran, Aliza; Aslam, Kiran; Attaullah, Anita; Syed, Areeba; Sheikh, Sara; Shams, Misbah (International Journal Of Community Medicine And Public Health, 2024)
Background: Responsive interactions among caregivers and newborns are essential for positive and optimal growth and development. The aim of this cross-sectional study was to develop and validate a short responsive interaction tool (SRIS) to assess caregiver responsiveness of newly delivered mothers. Methods: The SRIS consists of twenty elements that are used to classify new-born handling, interactions, consoling techniques, engagement, and distress. High reliability and internal consistency were shown in the data gathered from 257 mothers (Cronbach’s alpha=0.8354). The scale’s one-dimensional structure was discovered through construct validity analysis, demonstrating the consistency of the scale’s evaluation of response interactions. Results: The results indicate that the valid and reliable instrument for gauging the responsiveness of caregivers during their initial contact with neonates. It provides a useful and approachable method with possible uses in healthcare settings and research for evidence-based parenting interventions. Conclusions: To improve the tool’s generalizability and usefulness in fostering early childhood development and parental engagement, further research is necessary to validate it across a variety of contexts.